Overexpression of miR-506-3p reversed doxorubicin resistance in drug-resistant osteosarcoma cells - Xinru Wang; Rumeng Ding; Zhe Fu; Meng Yang; Duolu Li; Yubing Zhou; Chongzhen Qin; Wenda Zhang; Liuzhe Si; Jingmin Zhang; Yuna Chai (Frontiers Media S.A., 2024)
Background and objective: Osteosarcoma is a common primary malignant tumor of bone, and doxorubicin is one of the most widely used therapeutic drugs. While the problem of doxorubicin resistance limits the long-term treatment benefits in osteosarcoma patients. The role of miRNAs and their target genes in osteosarcoma have become increasingly prominent. Currently, there is no report on miR-506-3p reversing doxorubicin resistance by targeting STAT3 in osteosarcoma. The purpose of this study was to investigate the molecular mechanism that overexpression of miR-506-3p reverses doxorubicin resistance in drug-resistant osteosarcoma cells.Methods: Doxorubicin-resistant osteosarcoma cells (U-2OS/Dox) were constructed by intermittent stepwise increasing stoichiometry. The target genes of miR-506-3p were predicted by bioinformatics approach and the targeting relationship between miR-506-3p and STAT3 was detected using dual luciferase reporter assay. U-2OS/Dox cells were treated with miR-506-3p overexpression and STAT3 silencing respectively. Then Western blot and RT-qPCR were used to detect the protein and mRNA expression levels of JAK2/STAT3 signaling pathway, drug-resistant and apoptotic associated molecules. The migration and invasion were assessed by cell scratch assay and transwell assay. The cell proliferative viability and apoptosis were investigated by CCK8 assay and flow cytometry assay.Results: U-2OS/Dox cells were successfully constructed with a 14.4-fold resistance. MiR-506-3p is directly bound to the 3'-UTR of STAT3 mRNA. Compared with U-2OS cells, the mRNA expression of miR-506-3p was reduced in U-2OS/Dox cells. Overexpression of miR-506-3p decreased the mRNA expression levels of JAK2, STAT3, MDR1/ABCB1, MRP1/ABCC1, Survivin and Bcl-2, and decreased the protein expression levels of p-JAK2, STAT3, MDR1/ABCB1, MRP1/ABCC1, Survivin and Bcl-2, and conversely increased Bax expression. It also inhibited the proliferation, migration and invasion of U-2OS/Dox cells and promoted cells apoptosis. The results of STAT3 silencing experiments in the above indicators were consistent with that of miR-506-3p overexpression.Conclusion: Overexpression of miR-506-3p could inhibit the JAK2/STAT3 pathway and the malignant biological behaviors, then further reverse doxorubicin resistance in drug-resistant osteosarcoma cells. The study reported a new molecular mechanism for reversing the resistance of osteosarcoma to doxorubicin chemotherapy and provided theoretical support for solving the clinical problems of doxorubicin resistance in osteosarcoma.